2013
DOI: 10.1371/journal.pone.0068887
|View full text |Cite
|
Sign up to set email alerts
|

WRINKLED1, A Ubiquitous Regulator in Oil Accumulating Tissues from Arabidopsis Embryos to Oil Palm Mesocarp

Abstract: WRINKLED1 (AtWRI1) is a key transcription factor in the regulation of plant oil synthesis in seed and non-seed tissues. The structural features of WRI1 important for its function are not well understood. Comparison of WRI1 orthologs across many diverse plant species revealed a conserved 9 bp exon encoding the amino acids “VYL”. Site-directed mutagenesis of amino acids within the ‘VYL’ exon of AtWRI1 failed to restore the full oil content of wri1-1 seeds, providing direct evidence for an essential role of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
149
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 33 publications
1
149
0
Order By: Relevance
“…The gray box indicates AtWRI1 and its presumed ortholog in B. distachyon. addition, the sequence VYL present in the first AP2 domain of AtWRI1, which is essential for its function (Ma et al, 2013), was also conserved in BdWRI1 (Supplemental Fig. S1).…”
Section: Overexpression Of Bdwri1 Increases Grain Tag Content In B Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The gray box indicates AtWRI1 and its presumed ortholog in B. distachyon. addition, the sequence VYL present in the first AP2 domain of AtWRI1, which is essential for its function (Ma et al, 2013), was also conserved in BdWRI1 (Supplemental Fig. S1).…”
Section: Overexpression Of Bdwri1 Increases Grain Tag Content In B Dmentioning
confidence: 99%
“…The Arabidopsis wri1 mutant has an 80% reduction of seed oil content (Focks and Benning, 1998), whereas overexpression of WRI1 increases seed oil content by 10% to 20% (Cernac and Benning, 2004). WRI1 orthologs from maize (Zea mays), rape (Brassica napus), and oil palm (Elaeis guineensis) have been shown to be involved in TAG production in embryos or fruit mesocarps, and their overexpression leads to increased seed oil content (Liu et al, 2010;Shen et al, 2010;Pouvreau et al, 2011;Ma et al, 2013;van Erp et al, 2014). Ectopic expression of WRI1 has also been used to stimulate oil production in nonseed tissues in both Arabidopsis and tobacco (Nicotiana tabacum; Cernac and Benning, 2004;Sanjaya et al, 2011;Dussert et al, 2013;Kelly et al, 2013;Vanhercke et al, 2014;Grimberg et al, 2015;Ma et al, 2015).…”
mentioning
confidence: 99%
“…Later, WRI1 orthologs were isolated from several crops including maize (Zea mays), rapeseed (Brassica napus), palm (Elaeis guineensis), and cotton (Gossypium spp.) (Ma et al 2013;Shen et al 2010;Pouvreau et al 2011;Qu et al 2012;Wu et al 2014). It has been reported that the seed oil contents in transgenic Arabidopsis, rapeseed, and maize overexpressing AtWRI1 or WRI1 orthologs increase by approximately 10-30 % (Cernac and Benning 2004;Liu et al 2010;Shen et al 2010;Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, WRINKLED1 (WRI1), which is known as an important regulator in Arabidopsis seed development, specifies the activities of genes encoding most key enzymes involved in late stages of glycolysis and fatty acid biosynthesis (Focks and Benning, 1998;Baud et al, 2007;Maeo et al, 2009;Ma et al, 2013).…”
mentioning
confidence: 99%